2020
DOI: 10.3390/f11111160
|View full text |Cite
|
Sign up to set email alerts
|

The Liriodendron chinense MKK2 Gene Enhances Arabidopsis thaliana Salt Resistance

Abstract: To adapt and sense environmental perturbations, including a variety of biotic and abiotic stress conditions, plants have developed disparate regulatory pathways. Mitogen-activated protein kinase (MAPK or MPK) signaling cascades are found widespread across the eukaryotic kingdoms of life. In plants, they may regulate signaling pathways aimed at resisting the stressful effects of low temperature, salt damage, drought, touch, and mechanical damage. To date, no conclusive studies into Liriodendron chinense (Hemsl.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The importance of the MKK2 gene role in plant protection has been shown against salt (Chen et al, 2020) and low temperature (Gao et al, 2017). In this study, the MKK2 gene was targeted for integrating BleoR into the poplar genome by improving HDR efficiency with Zeocin resistance (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of the MKK2 gene role in plant protection has been shown against salt (Chen et al, 2020) and low temperature (Gao et al, 2017). In this study, the MKK2 gene was targeted for integrating BleoR into the poplar genome by improving HDR efficiency with Zeocin resistance (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…In eukaryotic kingdoms, Mitogen-activated protein kinase (MAPK or MPK) signaling is broadly crossed. In plants, they may direct signal pathways to resist the impacts of drought, cold, salt, scratch, and mechanical damage(Chen et al, 2020). Moreover, scientists have shown that MAPKs direct cellular responses against heat shock, osmotic, and other environmental stresses (Mohanta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified genes can be clustered into different types. Some genes are regarded as stress marker genes, and others as ethylene, jasmonic acid, and auxin signaling [47,48].…”
Section: Salt Stress and Signaling Pathwaysmentioning
confidence: 99%
“…Therefore, our objective was to examine the effects of HDR cofactor overexpression ( CtIP and MRE11 ) [ 15 ] and simultaneous disruption of the NHEJ promoter XRCC4 [ 18 ] on knock-in efficiency using the MKK2 gene as a case study. Mitogen-activated protein kinases (MAPKs or MPKs) like MKK2 are involved in several key pathways responding to stresses, including disease, drought, cold, heat shock, osmotic, and salt stresses [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%